Design of Security System Device for Motorized Vehicles through the Telegram Messenger Application and Updating GPS Locations on Smartphones in Real Time with IoT-based Smart Vehicles - Haris Isyanto; Husnibes Muchtar; Rasma Rasma; Adam Rasyid Dinata (Journal of Electrical Technology UMY, 2022)
Currently, the number of cases of motorized vehicle theft is increasing. Lack of double security, when left by the owner, is one of the factors that cause vehicles to be easily stolen. Based on these problems, we designed a motorized vehicle security system device that can monitor the condition and update the vehicle location with a smartphone through Global Positioning System (GPS). Furthermore, it can send an active alarm in the form of a buzzer alarm when there is an indication of the danger of vehicle theft. Furthermore, send notifications to the user so that the user immediately locks the vehicle by controlling it remotely in real-time through the Internet of Things (IoT)-based Smart Vehicle Security System using the Telegram Messenger Application and Google Maps (GMaps). The results of testing the response time show that the best performance is very responsive at 2.776 seconds in monitoring and controlling the vehicle. Moreover, the results of testing the vehicle distance position with GMaps and GPS obtained the best performance with a success rate percentage of 97.35% and an error rate percentage of 2.65%. It aims to make vehicle owners feel safe and comfortable and prevent motorized vehicle theft.